A contribuição da governança municipal para a implementação dos objetivos do desenvolvimento sustentável: a extrafiscalidade ambiental como política pública para os municípios cearenses - Santos, Lucas Antunes (2022)
The insufficiency of private actors to implement actions to maximize environmental protection and the internalization of negative externalities of market production open space for the positive action of the State, expanding its scope of action (qualitative) and optimizing the creation of public policies aimed at protection of the environment. The existence of a globalized international system makes the economy increasingly interdependent. As a result, new behavioral requirements arise, transforming the way human beings relate to the world and its resources. National challenges become locally important and local challenges become transnationally important. Faced with the imminence of a climatic collapse, it is believed that the participation of municipalities is essential to stop environmental degradation, because, through them, it is possible to identify weaknesses and propose strategic actions for development. It is evident, through this work, how such federative entities can incorporate the goals of the 2030 Agenda into their legislation. imprinting a new dynamic for the formulation and implementation of public policies, based on multilevel governance and sustainability. Although the transnational goals assumed by Brazil serve as a guide for the performance of the public manager at all levels of government, it is argued that, without the participation of the local government, it would be impossible to achieve them. As they have less political complexity – compared to national governments – it becomes more tangible for municipalities to implement the SDGs. In this sense, concern for the environment emerges among the SDGs and requires that the environmental issue be assimilated and faced responsibly by the economic order. In practical terms, the State can intervene in society and the economy through extrafiscal environmental policy. Using this function, the State manages to encourage the taxpayer to adopt more obsequious postures to the environment, strengthening the individual's relationship with the natural system in which he is inserted. Based on these premises, the possibility/feasibility of municipalities to promote the location of the SDGs is defended through the inclusion of environmental extrafiscality in the IPTU, ITBI and ISSQN laws, in order to boost the sustainable development of cities and improve quality. of life of the population. Bibliographic and documentary research is used as a methodology, with the analysis of books, legal articles, international documents and the pertinent legislation. The study is pure and qualitative in nature, with a descriptive and exploratory purpose.